The Ethics of Persuasion: Cognitive Bias and Platform Design in Emerging E Commerce Markets - Muharam, Husni (Moneta : Journal of Economics and Finance, 2024)
This study investigates the psychological dynamics influencing consumer behavior within Indonesia’s digital commerce ecosystem, emphasizing how anchoring, social proof, impulsivity, and status quo bias shape online purchasing decisions. As mobile first commerce and fintech adoption accelerate across Southeast Asia, consumers increasingly rely on cognitive shortcuts, leading to predictable and sometimes suboptimal buying behaviors. The research aims to localize these behavioral tendencies by examining their cultural, technological, and demographic triggers. A mixed-methods approach was employed, combining experimental surveys, literature synthesis, and platform-based observational data to examine how pricing cues, interface design, social validation, and fintech adoption interact with cognitive biases in shaping decisions. The findings show that anchoring is amplified by mobile-first interfaces and urgency-driven promotions, especially among younger and lower-income users; social proof exerts strong influence in collectivist cultures; impulsivity is intensified by fintech tools facilitating immediate gratification; and status quo bias reinforces habitual platform dependence. Collectively, these dynamics distort price perception, reduce market efficiency, and promote habitual rather than evaluative purchasing. This study contributes by offering a localized behavioral framework for Southeast Asia’s e-commerce markets and providing actionable implications for ethical platform design, evidence-based regulatory frameworks, and targeted consumer education. Transparency in promotional logic, educational nudges, and friction points are suggested as strategies to mitigate cognitive distortions while fostering consumer-centered growth.